The Performative Manuscript: Art, Agency and Public Ritual in Ottonian Mainz - Rodríguez Viejo, Jesús (The journal of ecclesiastical history, 2019)
The German city of Mainz under Archbishop Willigis (975-1011) witnessed a major flourishing of the arts, particularly in the field of architecture. During this period, a benedictional, now in St Gall, was also commissioned. Its only figurative content is an image of Christ in Majesty on its first folio. Taken as a case study, analysis of this permits an approach to the barely-explored concept of performativity in early medieval illuminated manuscripts. This Maiestas Domini, the list of blessings contained in the book and contemporary depictions of religious ceremonies invites consideration of the joint role that image and manuscript played in the dynamic liturgical rites during which the benedictional was handled.